Seismic Performance Of Reinforced Concrete School Buildings In Sabah - H. Sovester, H; M. I., Adiyanto (Universiti Malaysia Pahang, 2017)
One of the methods to evaluate the seismic performance is the nonlinear time history analysis where the structural models are imposed to the real or artificial earthquake ground motion records. Current practice only considers single earthquake in the analysis. However, in reality the earthquake tremors are always occur multiply. Ranau earthquake which occurred on 5th June 2015 was also not a single earthquake, but followed by several number of aftershock. This project investigated the performance of reinforced concrete school buildings in Sabah when subjected to multiple earthquakes. A total number of 3 models of school building which have 2, 3 and 4 storeys has been used for the project. . All models have been designed based on BS8110 to represent the existing reinforced concrete school buildings. A total of 7 ground motions for both single and multiple earthquake has been considered in nonlinear time history analysis conducted on all models. All models are assumed to be located in moderate seismic region in Sabah, Malaysia. Based on a series of nonlinear time history analyses, this study concludes that the action of multiple earthquake has contributed around 55% to 107% higher interstorey drift ratio compared to the single earthquake. Thus, multiple earthquake should be considered in order to design new buildings as well as the evaluation for maintenance and rehabilitation for existing buildings.